Corrosion behavior of carbon fiber reinforced polymer anode in simulated impressed current cathodic protection system with 3% NaCl solution. (1st June 2016) - Sun, Hongfang; Wei, Liangliang; Zhu, Miaochang; Han, Ningxu; Zhu, Ji-Hua; Xing, Feng
Highlights: CFRP operated stably at the applied current densities. The tensile strength of CFRP varied with applied charge density. The epoxy of CFRP was corroded during anodic. The appearance of carbon fiber showed no significant change. The degradation of CFRP may be attributed to the broken of CN bond of epoxy. Abstract: This study investigated the corrosion behavior and failure mechanism of carbon fiber reinforced polymer (CFRP) employed as an impressed current anode in 3% NaCl solution. The measured feeding voltage and potential indicated that CFRP operated stably at the applied current densities. The experimental results show that the tensile strength of CFRP decreases with increasing charge density. The corrosion rate is approximately 0.02 mm/day for a current density of 6.15 A/m 2 . The failure mechanism is due to corrosion of the epoxy in CFRP, where breakage of CN bonds in the epoxy matrix leads to depolymerization of the epoxy.